Violence infection (a study in image of sociology) - Abdul Redha Qetan, Talib (International Journal of Psychosocial Rehabilitation, 2020)
That what is dominated by the strategies of cultural hegemony today are new bets, at the heart of which are the use of image technology and harnessing its capabilities in the field of cross-border cultural production, languages, cultures, and nationalities where the image has become destructive in many aspects of its media and electronic uses. If noble human values were destroyed, humanity would have sacrificed so long to attain it. The researcher has posed a number of questions, including: What are the most important sources of the threat that violates the human security of the Iraqi individual? What are the most important results and indicators resulting from it? The results of the study showed that one of the sources of the threat that violates the human security of the Iraqi individual is the political conditions that the country is going through, where the sample response rate (18.6%) was recorded and the highest percentages were issued.